Keberadaan Mikroflora Alami Dalam Fermentasi Cuka Apel Hijau (Malus sylvestris Mill.) Kultivar Granny Smith - Risca Adelina Atro; Periadnadi Periadnadi; Nurmiati Nurmiati (Jurnal Biologi Universitas Andalas, 2015)
Research on The Presence of Natural Microflora in Fermentation of Green Apples Cider Vinegar (Malus sylvestris Mill.) Cultivars Granny Smith was conducted from February to June 2014 at Microbiology Research Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. The purpose of the research were to determine the Presence of the natural microflora (yeasts and bacteria) in fermentation of a Granny Smith apple cider vinegar and to determine the character of apple cider vinegar in terms of pH value dan sugar content. The results showed that the fermentation of apple cider vinegar was the Presence of the natural microflora (yeast as much as 1.8 x 106 cfu/ml and bacteria as much as 3.4 x 106 cfu/ml) and obtained with apple cider vinegar acid concentration (pH 3.13) with a residual sugar content (1.5% Brix) after 14 days of acetic acid fermentation.Keywords:       Natural Microflora, Granny Smith Apples, Apple Cider Vinegar